The Impact of DevOps on Efficiency and Innovation in Government Organizations - Omer Alrwais; Lama AlEkresh (Universitas Komputer Indonesia, 2026)
This study investigates how DevOps can enhance efficiency and foster innovation within public sector institutions. While widely adopted in the private sector to bridge software development and IT operations through collaboration and automation, DevOps remains underutilized in government frameworks. Focusing on Saudi Arabia's digital transformation under Vision 2030, this research utilizes surveys, interviews, and case studies to examine the core benefits and operational challenges of this methodology. The findings indicate that DevOps significantly accelerates service delivery and stimulates innovative public applications. However, cultural resistance and technical skill gaps present substantial barriers. The study concludes that structured training and strategic partnerships with private sector experts are essential for modernizing government services.